Restless giant : the United States from Watergate to Bush v. Gore - Patterson, James T. (New York : Oxford University Press, 2005)
A concise assessment of the 27 years between the resignation of Richard Nixon and the election of George W. Bush, weaving together social, cultural, political, economic, and international developments. We meet the era's many memorable figures--most notably, Ronald Reagan and Bill Clinton--and explore the "culture wars" where liberals and conservatives appeared to cut the country in two. Patterson describes how, when the Cold War finally ended, Americans faced bewildering new developments around the world. In exploring a wide range of cultural, social, and economic concerns, he shows how the persistence of racial tensions, high divorce rates, alarm over crime, and urban decay all led many writers to portray this era as one of decline. But he argues that our often unmet expectations caused many of us to view the era negatively, when in fact we were in many ways better off than we thought.--From publisher description.
The troubled 1970's -- Sex, families, stagflation -- The political world of the mid-1970s -- Carter, Reagan, and the rise of the right -- "Morning again in America" -- America and the world in the 1980's -- Bush 41 -- "Culture wars" and "decline" in the 1990's -- Immigration, multiculturalism, race -- Political wars of the early Clinton years -- Prosperity, partisanship, terrorism -- Impeachment and electoral crisis, 1998-2000.
Includes bibliographical references and index.
Keywords: United States -- History -- 1969-